The politics of crime and community - Hughes, Gordon, 1952- (Basingstoke [England] ; New York : Palgrave Macmillan, 2007)
Gordon Hughes offers a wide-ranging and authoritative analysis of th e complex issues and debates in the politics of crime and community saf ety. Drawing on new research and evidence, the text adopts an original comparativist perspective to the understanding of the culture of contem porary society.
Includes bibliographical references (p. 213-225) and index.
Keywords: Crime prevention -- Great Britain; Community life -- Great Britain; Communitarianism -- Great Britain; Offenses against public safety -- Great Britain; Great Britain -- Social conditions; Great Britain -- Politics and government